Evaluation of Frequency of Congenital Hypothyroidism and its Risk Factors in Newborns in Kohgiluyeh County (2013-2016) - Piraee, Elahe; Azarbakhsh, Habibollah; Shakolohi, Zahra (Revista Publicando, 2018)
Introduction: Congenital hypothyroidism is one of the most common endocrine diseases and is one of the most important causes of mental retardation. The present study was conducted to determine the prevalence of hypothyroidism and its effective factors in Kohgiluyeh County from 2013 to 2016. Materials and Methods: This case-control study was performed on newborns born in Kohgiluyeh County who participated in the congenital hypothyroid screening from March 2013 to February 2016. Neonates with TSH (Thyroid-Stimulating Hormone) were healed more than or equal to 5. Then, their serum TSH level was measured. Newborns with a TSH level greater than or equal to 10 mu / L were considered as congenital hypothyroidism. For each patient, three healthy children were selected as controls. SPSS software was used to analyze the data. Results: The incidence of disease was 5.56 in 1000 live births during these four years, of which 1 case was diagnosed in 180 live births. Boys were 20.6% more likely to have hypothyroidism than girls. There was no significant relationship between the type of delivery and the incidence of hypothyroidism (P> 0.05). Also, there was a significant relationship between the history of hypothyroidism in the family and hypothyroidism (P = 0.001). Conclusion: The prevalence of congenital hypothyroidism in Kohgiluyeh County city is more than national and global statistics, which has concerns (1: 180 live births).